A Digital-Based Islamic Guidance and Counseling Service Model: The HiDende Application Innovation for Building a Sexual-Violence-Free Campus - Syamsul Hadi; Dwi Widarna Lita Putri (Universitas PGRI Yogyakarta, 2026)
Cases of sexual violence continue to occur in higher education institutions in Indonesia, with 1,011 cases reported across sixteen campuses, including universities in West Nusa Tenggara. Given this condition, this study is important to conduct by developing a digitally based Islamic Guidance and Counseling service model, in the form of the HiDende application, to support the creation of a campus free of sexual violence. This research aims to develop a model for the prevention and handling of sexual violence through digital-based Islamic Guidance and Counseling services using the HiDende application. The study employs a Research and Development approach with the ADDIE design. The results yield a digitally based Islamic Guidance and Counseling service model, namely the HiDende cybercounseling application. Research findings indicate that the application integrates preventive strategies through interactive educational content and curative services through anonymous counseling with psychologists. The study concludes that the HiDende Mobile App provides a practical and adaptive digital Islamic Guidance and Counseling service model. The implications suggest that HiDende can serve as a strategic digital solution for universities in preventing and addressing sexual violence effectively and sustainably. Keywords: islamic guidance and counseling, digital counseling, hidende application, sexual violence, college